CD4+CD25+ T cells maintain homeostasis by promoting TER-119 cell development and inhibiting T cell activation - Rifai, Muhaimin (Journal of Tropical Life Science, 2014)
CD4+CD25+ regulatory T cells involved in the regulation of self-tolerance and normality of homeostasis. CD122 deficient mice are model animals that have an abnormal immune system characteristically have a high number of activated T cells and TER-119 cell decreased. Here we showed evidence that the transfer of CD4+CD25+ regulatory T cells derived from normal mice to CD122-defficient neonates prevent the development of activated memory T cells and elicit TER-119 differentiation. Bone marrow reconstitution derived from CD122-/- mice to normal mice resulting tolerance to individual that genetically different. Importantly, CD4+CD25+ regulatory T cells derived from normal mice can replace CD4+CD25+ cells derived from CD122-/- mice. The results of this experiment suggest that regulatory T cells from normal mice exert a critical role in maintaining peripheral tolerance and controlling hematopoietic disorder.